2021
DOI: 10.1039/d0ra09369f
|View full text |Cite
|
Sign up to set email alerts
|

Copper–CNT interfacing with Cu-doped polydopamine in CNT carpet: copper nucleation and resistance decrease upon soft annealing

Abstract: The annealing of carpets of CNT coated with Cu-doped polydopamine lowers the carpets sheet resistance and induces the reduction of Cu ions into metallic Cu particles nucleating at the CNT surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…4) as expected for large diameter MWCNT 6,7,21 and has a similar value independent of the coating or compression steps. Compared to the TCR of carpets containing oxidized CNT with a length of 200 mm and a diameter of 80-90 nm (see our previous paper 21 ), we nd here a similar TCR in our oxidized CNT systems (800 mm, 80-90 nm), suggesting that the variation of the CNT length does not drastically affect the TCR. Furthermore, in our previous paper, we also observed that the TCR of CNT coated with Cu-doped Pda was lower than un-coated CNT.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…4) as expected for large diameter MWCNT 6,7,21 and has a similar value independent of the coating or compression steps. Compared to the TCR of carpets containing oxidized CNT with a length of 200 mm and a diameter of 80-90 nm (see our previous paper 21 ), we nd here a similar TCR in our oxidized CNT systems (800 mm, 80-90 nm), suggesting that the variation of the CNT length does not drastically affect the TCR. Furthermore, in our previous paper, we also observed that the TCR of CNT coated with Cu-doped Pda was lower than un-coated CNT.…”
Section: Resultssupporting
confidence: 75%
“…In our previous work, 21 we used XPS to evidence the presence of the Cu-doped Pda on our CNT aer a similar coating protocol. Here, Cu and Ni were directly conrmed by EDX (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For SWCNTs, the C1s and O1s peaks were located at 284.8 eV and 532.3 eV, respectively. 38 For PEI/SWCNT, in addition, the C1s (285.1 eV) and O1s (532.1 eV) peaks, a new peak at 399.9 eV is ascribed to N1s. For [Ag(NH 3 ) 2 ] + -PEI/SWCNT-2, the N1s peak was red-shifted from 399.9 eV to 399.3 eV, which might be ascribed to the interaction between silver ammonia and PEI.…”
Section: Resultsmentioning
confidence: 97%